Optimization of process parameters for the production of jaggery infused osmo-dehydrated coconut chips. (July 2021) - Pravitha, M.; Manikantan, M.R.; Ajesh Kumar, V.; Beegum, Shameena; Pandiselvam, R.
Abstract: Coconut slices were converted into healthy coconut chips by replacing conventional osmotic agent with jaggery to counteract the health deteriorating effect of refined sugar. The optimal processing condition to yield the desired product was determined by employing a Box-Behnken design based on independent variables: drying temperature (50–70 °C), jaggery solution concentration (45–55 °Brix), and slice thickness (0.50–1.00 mm). The simultaneous optimization of these processing parameters was done based on the responses: final moisture content, drying rate, rehydration ratio, crispness, appearance, taste and overall acceptability. Further, the sample prepared at the optimized condition (drying temperature - 66.22 °C, slice thickness - 0.55 mm and jaggery solution concentration - 46.18 °Brix) was characterized and compared with traditional refined sugar osmosed coconut chips. Proximate and mineral analysis of the optimized sample suggested that incorporating a new osmotic agent, jaggery, has improved the nutritional quality of the chips with higher consumer acceptability. Highlights: Coconut chips were prepared by osmo-convective drying with jaggery as osmotic medium. Process parameters were optimized based on drying characteristics and sensory attributes. Developed jaggery osmosed coconut chips were rich in minerals compared to traditional coconut chips.